Educational innovations in Finnish and European contexts : an analysis of the aims and outcomes of 'the European Observatory' of the European Commission (1994-1998) - Tella, Seppo, 1947-; Tirri, Kirsi, 1961- (Helsinki : University of Helsinki, 1999)
Abstrakti.
Keywords: European Observatory of Innovations in Education and Training; innovaatiot; kasvatus; koulutus; Eurooppa